2019
DOI: 10.3390/cancers11010102
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Pannexin 1 Reduces the Tumorigenic Properties of Human Melanoma Cells

Abstract: Pannexin 1 (PANX1) is a channel-forming glycoprotein expressed in many tissues including the skin. PANX1 channels allow the passage of ions and molecules up to 1 kDa, including ATP and other metabolites. In this study, we show that PANX1 is highly expressed in human melanoma tumors at all stages of disease progression, as well as in patient-derived cells and established melanoma cell lines. Reducing PANX1 protein levels using shRNA or inhibiting channel function with the channel blockers, carbenoxolone (CBX) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 66 publications
3
58
0
Order By: Relevance
“…This scenario is supported by data from recent studies on testicular cancer cells, where PANX1 inhibition downregulates EMT genes, upregulates E-cadherin, downregulates MMP-9, and decreases cell invasion [80]. Freeman et al showed that decreasing PANX1 protein levels, in melanoma cells, using shRNA or blocking PANX1 channel using PBN or carbenoxolone decreased cell growth, migration, and invasiveness, probably through the Wnt/β-catenin pathway [83].…”
Section: Discussionmentioning
confidence: 83%
“…This scenario is supported by data from recent studies on testicular cancer cells, where PANX1 inhibition downregulates EMT genes, upregulates E-cadherin, downregulates MMP-9, and decreases cell invasion [80]. Freeman et al showed that decreasing PANX1 protein levels, in melanoma cells, using shRNA or blocking PANX1 channel using PBN or carbenoxolone decreased cell growth, migration, and invasiveness, probably through the Wnt/β-catenin pathway [83].…”
Section: Discussionmentioning
confidence: 83%
“…Precise regulation of purinergic signalling via PANX1 is critical in many diverse cell types, including maintaining neural stem cell populations [76][77][78], regulating the development of immature neurons [79,80], tumorigenicity [81,82] and metastasis [83] of several cancers [84].…”
Section: Discussionmentioning
confidence: 99%
“…Precise regulation of purinergic signalling via PANX1 is critical in many diverse cell types, including maintaining neural stem cell populations [7678], regulating the development of immature neurons [79,80], tumorigenicity [81,82] and metastasis [83] of several cancers [84]. Macropinocytosis is also intimately involved in regulating these processes ([311], reviewed in Finicle et al [12] and Bloomfield and Kay [13]).…”
Section: Discussionmentioning
confidence: 99%
“…Biopsies were dissected by a pathologist immediately after surgery. Primary melanoma cells were isolated and cultured, and total cell lysates were prepared as described [53].…”
Section: Methodsmentioning
confidence: 99%